Содержание факторов роста в пульпе постоянных зубов при хроническом пульпите (Эндодонтия Today)
In the present work the maintenance of a major fibroblast growth factor-β, insulin growth factor-1, transforming growth factor -1β in gomogenates pulps of a constant teeth in norm has been studied and at an chronic inflammation. Results have shown that in the inflamed pulp the tendency to increase in the maintenance insulin growth factor-1 and to decrease in quantity of a major fibroblast growth factor - β, transforming growth factor -1β. The obtained data testifies to decrease proliferative activity of cages of a pulp of a tooth against a chronic inflammation.